Address negative perceptions about higher education. Issue 2 (23rd April 2018) - Hope, Joan
Abstract : On top of changing demographics and declines in international student enrollment, college and university enrollment divisions face increasing questions about whether going to college is worth it. Many doubts students and parents have relate to the cost of completing a degree. It's clear that students and parents think college must be about job preparation, said Paul Marthers, vice provost for enrollment management at Emory University. There's growing sensitivity around indebtedness, added Scott Baumler, enrollment systems analyst at Grinnell College.